2018
DOI: 10.1002/jlb.3hi1017-405rr
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: A reduction in DHA-derived mediators in male obesity contributes toward defects in select B cell subsets and circulating antibody

Abstract: Obesity dysregulates B cell populations, which contributes toward poor immunological outcomes. We previously reported that differing B cell subsets are lowered in the bone marrow of obese male mice. Here, we focused on how lipid metabolites synthesized from docosahexaenoic acid (DHA) known as specialized pro‐resolving lipid mediators (SPMs) influence specific B cell populations in obese male mice. Metabololipidomics revealed that splenic SPM precursors 14‐hydroxydocosahexaenoic acid (14‐HDHA), 17‐hydroxydocosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 76 publications
3
40
0
Order By: Relevance
“…We demonstrated that high LA intake decreased plasma levels of SPM precursors, 14-HDHA and 17-HDHA, and their downstream products MaR1 and PDX, known for their anti-inflammatory and pro-resolving properties. Our data are in lines with recent evidence showing that obesity was associated with a downregulation of EPA-and DHA-derived SPM [21,[67][68][69]. The authors have linked the n-3 derived…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrated that high LA intake decreased plasma levels of SPM precursors, 14-HDHA and 17-HDHA, and their downstream products MaR1 and PDX, known for their anti-inflammatory and pro-resolving properties. Our data are in lines with recent evidence showing that obesity was associated with a downregulation of EPA-and DHA-derived SPM [21,[67][68][69]. The authors have linked the n-3 derived…”
Section: Discussionsupporting
confidence: 92%
“…derivatives at the expense of n-3 PUFA derivatives as described in high fat diet studies [21,67]. We demonstrated that high LA intake decreased plasma levels of SPM precursors, 14-HDHA and 17-HDHA, and their downstream products MaR1 and PDX, known for their anti-inflammatory and pro-resolving properties.…”
Section: Discussionsupporting
confidence: 57%
“…SPMs are synthesized predominately from the n-3 polyunsaturated fatty acids (PUFAs) eicosapentaenoic (EPA) and docosahexaenoic acid (DHA) 1 . There is growing evidence from humans and mouse models that obesity impairs the biosynthesis of SPMs and their precursors [5][6][7][8] . The loss of SPMs contributes toward a range of obesity-related complications including chronic inflammation, hepatic steatosis, insulin resistance, susceptibility to infection, and delayed wound healing 6,[9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that routinely used sample preparation and LC/MS methods will not allow for the detection of all compounds. We address this in our own lab by developing targeted methods for compounds (e.g., oxylipins, nucleotides [53,54]) that are not typically detected in our LC/MS profiling studies. The purpose of STSDBs is not to provide 100% coverage of a particular metabolome; rather, if a compound can be detected using standard methods, it will become part of an STSDB.…”
Section: Limitations Of Stsdbsmentioning
confidence: 99%